73.8k views
4 votes
Assume f(x) = 3 - x. Find f --(-1).-441/3Please help me I don’t know if my answer is correct

Assume f(x) = 3 - x. Find f --(-1).-441/3Please help me I don’t know if my answer-example-1

1 Answer

3 votes

The first step is to find the inverse of the given function.

To do it, you need to solve the given equation for x, it means isolate x to one of the sides of the equal sign, this way:


\begin{gathered} f(x)=3-x \\ f(x)+x=3 \\ x=3-f(x) \end{gathered}

Now, change x for f^-1(x) and f(x) for x:


\begin{gathered} x=3-f(x) \\ f^(-1)(x)=3-x \end{gathered}

Now, find the value of the inverse function when x=-1. To do it, replace every x in the equation for -1:


\begin{gathered} f^(-1)(-1)=3-(-1) \\ f^(-1)(-1)=3+1 \\ f^(-1)(-1)=4 \end{gathered}

The answer is 4.

User Eric Blum
by
5.6k points